PENGARUH KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA PEGAWAI HONORER BAGIAN LANTAS DI DINAS PERHUBUNGAN KABUPATEN OGAN KOMERING ULU - Yopi Yunsepa; Achmad Johan Mushoddiq; Soni Damansyah (STIE DWI SAKTI BATURAJA, 2022)
The purpose of this study was to determine the effect of organizational commitment on organizationalcitizenship behavior in temporary employees of the Then section of the Department of Transportation inOgan Komering Ulu Regency. This study used a descriptive method with data collection techniques throughobservation, interviews, questionnaires, documentation and literature study. The analysis technique used isqualitative and quantitative data analysis techniques. The results of data processing obtained from thesimple linear regression equation are Y = 0.438 + 0.870 X. The correlation value is 0.779. It can beinterpreted that the correlation between organizational commitment variable (X) and organizationalcitizenship behavior (Y) is strong. The result of the coefficient of determination or R Square is 0.606 orequal to 60.6%. This shows that the contribution of organizational commitment variable (X) toorganizational citizenship behavior (Y) is 60.6%, while the remaining 39.4% is explained by other factorsnot explained in this study. The results of the t test show that tcount is worth 6.204, thus tcount> ttable(6.204 > 2.0595) this means that Ho is rejected and Ha is accepted, meaning that there is an influence oforganizational commitment (X) on organizational citizenship behavior (Y) in part-time honoraryemployees at the Ogan Komering Ulu District Department of Transportation.